The Short-Run Behavior of Physical Productivity and Average Hourly Earnings - Kerr, Clark (The Review of Economics and Statistics, 1949)
and rates,' thought by many economists to be a highly desirable match, do not appear to possess those characteristics of compatibility upon which the perfect marriage depends. Disconcertingly, in the short-run, they display a clear tendency to move either in opposite directions or, if in the same direction, at quite different rates. The postwar experience in this country and the possibility of continuing high levels of employment in the future, in an economy imperfectly protected from the raids of pressure groups, have caused intensified concern over the relationships of these two variables. We may appropriately inquire whether it is reasonable to expect man-hour output and money wages, from year to year or over moderately longer periods, to progress hand in hand.2 It is frequently suggested that they should move in close harmony over some period of time, since, if they did, price would be facilitated. Lord Keynes was particularly influential in popularizing this view.3 Sir William Beveridge ' and Professors Hansen 5 and Slichter,6 among others, have added the weight of their support. These normative proposals of economists have been elevated to the level of a national policy by the Council of Economic Advisers which advocates wage increases which are in line with productivity trends. 7 This article is not concerned with whether this norm is a desirable one or not, but rather with a realistic appraisal of the likelihood of its being followed. The time period under consideration is the short-run. Over relatively long periods the three quarters of a century before World War I and the quarter of a century after it manhour output and wages increased by approximately the same amount. The short-run movements of the two variables, however, are also important and have an effect on the operation of the economic system on costs, profits, prices, and real wages. Significant short-term departures from the pattern of the long-term movements will be shown to have occurred. It will be suggested that, given the business cycle and our present collective bargaining institutions and practices, the short-run gearing of wages to productivity in the future is unlikely to be achieved with any great precision. The distinct impact of the business cycle on productivity and on wages, a neglected consideration, and the realities of the setting process make implementation of the policy more difficult than commonly supposed. The two variables almost inevitably act 1 The term productivity will be used throughout to mean physical, not value, productivity; and rates to mean money, not real, wages. 2 Real wages per hour and man-hour output, unless there is some change in the earners' share of the national product, must change approximately together in the longrun and in fact they do. (See Jules Backman and Martin R. Gainsbrugh, Productivity and Living Standards, Industrial and Labor Relations Review, January I949.) This present article is not concerned with the relationship of real wages to man-hour output, nor with long-run historical relationships between money wages and productivity in the economy at large, nor with long-run relationships in individual industries. Professor Hansen has noted, for example, that over a period of about seventy-five years prior to World War I money wages rose commensurate with improved productivity. (A. H. Hansen, Wages and Prices: The Basic Issue, New York Times Magazine, January 6, I946.) Professor Dunlop has discussed the longrun impact of productivity on inter-industry differentials and demonstrated that it has had a pronounced effect. (John T. Dunlop, Productivity and the Wage Structure, Income, Employment and Public Policy, New York, I948.) aJ. M. Keynes, The General of Employment, Interest and Money (New York, I936), p. 27I. See also Seymour E. Harris, Attack on Laissez Faire and Classical Economics and Wage Theory in The New Economics: Keynes' Influence on and Public Policy, edited by Seymour E. Harris (New York, I947), pp. 554-56. For a discussion of earlier suggestions along the same lines as Keynes, see A. G. Pool, Wage Policy in Relation to Industrial Fluctuations (New York, I938), p. 286 ff. 'William H. Beveridge, Full Employment in a Free Society (New York, I945), p. 200. Op. cit. He views stability of efficiency-wages as the appropriate goal for policy. (Monetary and Fiscal Policy, New York, I949, Ch. 8.) 6Sumner H. Slichter, The Challenge of Industrial Relations (Ithaca, N. Y., I947), p. 89. See also Basic Criteria Used in Wage Negotiations, Chicago Association of Commerce and Industry, I947, pp. 44-48. 7Council of Economic Advisers, The Annual Economic Review-January 1949, p. 45.